Подходы к созданию стандартных образцов для теплового неразрушающего контроля (ТНК) - Стороженко, В. А.; Хорло, Н. Ф.; Мешков, С. Н.; Маслова, В. А. (ХНУРЭ, 2005)
One of actual problems of development of a thermal method of not destroying control in Ukraine, namely - creation of standard samples for adjustment and checkings of IR-cameras is considered. It is offered to use the decisions known in the ultrasonic control as the prototype.
Keywords: метрология; измерительная техника